2020
DOI: 10.1038/s41598-020-76412-8
|View full text |Cite
|
Sign up to set email alerts
|

Multi-beam X-ray ptychography for high-throughput coherent diffraction imaging

Abstract: X-ray ptychography is a rapidly developing coherent diffraction imaging technique that provides nanoscale resolution on extended field-of-view. However, the requirement of coherence and the scanning mechanism limit the throughput of ptychographic imaging. In this paper, we propose X-ray ptychography using multiple illuminations instead of single illumination in conventional ptychography. Multiple locations of the sample are simultaneously imaged by spatially separated X-ray beams, therefore, the obtained field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Furthermore, Lo et al demonstrated X-ray linear dichroic ptychography and mapped the c-axis orientations of aragonite crystals [76]. Additionally, in 2020, Yao et al applied multiple illuminations to the method and successfully received an extended FOV [77].…”
Section: Coherent Diffraction Imagingmentioning
confidence: 99%
“…Furthermore, Lo et al demonstrated X-ray linear dichroic ptychography and mapped the c-axis orientations of aragonite crystals [76]. Additionally, in 2020, Yao et al applied multiple illuminations to the method and successfully received an extended FOV [77].…”
Section: Coherent Diffraction Imagingmentioning
confidence: 99%
“…Research by many groups has focused on boosting ptychographic performance. [4][5][6][7][8][9][10] Among suggestions, socalled multi-beam ptychography makes use of multiple probes in parallel. [6][7][8][9][10] This approach offers an increase in field of view by a factor as large as the number of implemented X-ray probes for the same exposure time and resolution.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Among suggestions, socalled multi-beam ptychography makes use of multiple probes in parallel. [6][7][8][9][10] This approach offers an increase in field of view by a factor as large as the number of implemented X-ray probes for the same exposure time and resolution. It uses more photons from the source at the cost of encoding more information in the same diffraction patterns, which lowers the redundancy in the dataset.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 This can be achieved because each beam only needs to be coherent with itself and can be incoherent to all other beams. Multiple groups have demonstrated multi-beam x-ray ptychography using pinholes 9 or Fresnel zone plates 10 to create the beams. However, these schemes leave large parts of the incoming beam unused, as both the pinholes and the zone plates require a significant dead area between the individual optics.…”
mentioning
confidence: 99%